Hypovitaminosis D and severe hypocalcaemia: the rebirth of an old disease - Pedrosa, Cristina (BMJ Publishing Group, 2013)
Vitamin D deficiency, once thought to be eradicated, is becoming a frequent occurence in children, caused mainly by dietary insufficiency. The classical manifestation is rickets, but in infants severe hypocalcaemia may present as stridor, tetany, seizures or, rarely, heart disease. Here, we describe four infants who presented with complications of severe hypocalcaemia secondary to nutritional vitamin D deficiency. (1) Female, 4 months old, several spasms. (2) Male, 8 days old, generalised tonic-clonic seizure. (3) Male, 9 months old, tetany. (4) Male, 4 months old, cardiogenic shock. The cases highlight the importance of child vitamin D supplementation from birth and throughout childhood. We also note that the vitamin D state should be evaluated by the 25(OH)-D value and not the 1,25(OH)(2)-D.